Analyzing Patients' Complaints: Awakening of the Ethic of Belonging. (October 2019) - Ming, Yan; Wei, Holly; Cheng, Hong; Ming, Jie; Beck, Mark
Abstract : Nursing ethics are fundamental principles to nursing practice. The purpose of this study is to analyze patients' complaints filed against nurses from a nursing ethics perspective. This is a qualitative study. The data source is the patients' complaints filed in a university-affiliated hospital in China. The complaints are categorized into 4 themes: uncompassionate attitudes, unprofessional communication, disrespect of patient rights, and unsatisfactory quality of nursing care. The ethic of belonging reflects nurse-patient relations. Patients expect to be treated with dignity. This study sends out a call for nurse leaders and educators to reevaluate the practice and education of the nursing professional identity.